Myocardial inflammatory cells in cardiac amyloidosis - Simon, Philip; Behrens, Hans-Michael; Kristen, Arnt; Röcken, Christoph (Scientific reports, 2024)
Background: Immunoglobulin derived AL amyloidosis and transthyretin derived ATTR amyloidosis are the most common forms of cardiac amyloidosis. Both may present with cardiac arrhythmias, heart failure, and extracardiac symptoms. Disease outcome is often fatal. Recently, it was proposed that amyloid may cause cardiac inflammation. Here we tested the hypothesis that immune cell infiltration in cardiac tissue correlates with clinicopathological patient characteristics. Patients and methods: Myocardial biopsies from 157 patients with cardiac amyloidosis (46.5% AL, 53.3% ATTR) were immunohistochemically assessed for the presence and amount of T lymphocytes (CD3), macrophages (CD68) and neutrophils (MPO). Amyloid load, cardiomyocyte diameter, apoptosis (Caspase 3), necrosis (complement 9), and various clinical parameters were assessed and correlated with immune cell density. Results: Myocardial tissue was infiltrated with T lymphocytes (CD3), macrophages (CD68) and neutrophils (MPO) with variable amounts. Significant correlations were found between the number of macrophages and NYHA class. No correlations were found between the presence and amount of T lymphocytes, neutrophils and clinicopathological patient characteristics. Conclusion: The significant correlation between cardiac macrophage density and heart failure points towards a significant role of macrophages in disease pathology.